Multi-decadal variations in southern hemisphere atmospheric 14C: evidence against a Southern Ocean sink at the end of the Little Ice Age CO2 anomaly - Turney, C; Palmer, J; Hogg, A; Fogwill, C; Jones, R; Ramsey, C; Fenwick, P; Grierson, P; Wilmshurst, J; O'Donnell, A; Thomas, Z; Lipson, M (American Geophysical Union, 2016)
Northern Hemisphere-wide cooling during the Little Ice Age (LIA; 1650–1775 Common Era, C.E.) was associated with a ~5 ppmv decrease in atmospheric carbon dioxide. Changes in terrestrial and ocean carbon reservoirs have been postulated as possible drivers of this relatively large shift in atmospheric CO2, potentially providing insights into the mechanisms and sensitivity of the global carbon cycle. Here we report decadally resolved radiocarbon (14C) levels in a network of tree-ring series spanning 1700–1950 C.E. located along the northern boundary of, and within, the Southern Ocean. We observe regional dilutions in atmospheric radiocarbon (relative to the Northern Hemisphere) associated with upwelling of 14CO2-depleted abyssal waters. We find the interhemispheric 14C offset approaches zero during increasing global atmospheric CO2 at the end of the LIA, with reduced ventilation in the Southern Ocean and a Northern Hemisphere source of old carbon (most probably originating from deep Arctic peat layers). The coincidence of the atmospheric CO2 increase and reduction in the interhemispheric 14C offset imply a common climate control. Possible mechanisms of synchronous change in the high latitudes of both hemispheres are discussed.